PO 18194 - Functional and quality of life assessment of patients with ankle ulcers treated with complete Achilles tendon resection - Godinho Bordone Pires, Wrgelles; de Almeida Pinto, Roberto Zambelli; Carvalho Maia, Philipe Eduardo; Simões Castilho, Rodrigo; Vasconcelos de Carvalho, Felipe Daniel; Araújo Silva Lopes, Fernando (Scientific Journal of the Foot & Ankle, 2019)
Objective: The objective of this study is to perform a functional and quality of life assessment of patients subjected to debridement of ulcers in the posterior region of the ankle, which progressed to complete Achilles tendon resection without any type of tendon reconstruction or transfer. Methods: This is a case series of 4 patients, mostly diabetic, who underwent complete resection of an exposed and degenerated Achilles tendon due to ulcer in the posterior region of the ankle that precluded preservation given the need to control the infectious process considering the diagnosis of calcaneal osteomyelitis. This diagnosis was compatible with changes observed in the magnetic resonance imaging evaluation and was confirmed in cultures of bone tissue removed during debridement. The patients filled out the Brazilian Portuguese version of the Achilles Tendon Total Rupture Score (ATRS-BR) and 36-Item Short Form Survey (SF-36) during the postoperative period, and follow-up ranged from 6 to 24 months. The ATRS score ranges from 0 to 100, and the higher the scores are, the fewer symptoms and limitations the patients have. The SF-36 consists of 36 questions covering 8 domains: physical role functioning, physical functioning, bodily pain, general health perceptions, social role functioning, vitality, mental health and emotional role functioning. The items are independently assessed, and the total possible score is 100 points, which is indicative of the best health status. Results: All 4 Achilles tendons were approached. The mean age of the patients was 69.8 years. The mean score on the physical functioning section of the SF-36 was 63.8 points. When comparing the outcome with literature data, we observed that when patients with ulcers were compared with individuals of a similar age group, our study showed better results than previous studies. The mean score of the ATRS-BR was 46.3 points, which suggests a poor outcome. However, the patients had few complaints about their physical functioning, as shown in the SF-36 analysis. The decision not to perform Achilles tendon reconstruction was made jointly by the medical team and the patients and their families. Conclusion: Not reconstructing the Achilles tendon in patients, mostly elderly diabetic patients with posterior ankle ulcers, led to encouraging functional scores. The present study suggests that this type of ulcer treatment is a viable option for such populations.